Spatiotemporal changes in diffusivity and anisotropy in fetal brain tractography - Machado‐Rivas, Fedel; Afacan, Onur; Khan, Shadab; Marami, Bahram; Velasco‐Annis, Clemente; Lidov, Hart; Warfield, Simon K.; Gholipour, Ali; Jaimes, Camilo (Human brain mapping, 2021)
Population averaged diffusion atlases can be utilized to characterize complex microstructural changes with less bias than data from individual subjects. In this study, a fetal diffusion tensor imaging (DTI) atlas was used to investigate tract‐based changes in anisotropy and diffusivity in vivo from 23 to 38 weeks of gestational age (GA). Healthy pregnant volunteers with typically developing fetuses were imaged at 3 T. Acquisition included structural images processed with a super‐resolution algorithm and DTI images processed with a motion‐tracked slice‐to‐volume registration algorithm. The DTI from individual subjects were used to generate 16 templates, each specific to a week of GA; this was accomplished by means of a tensor‐to‐tensor diffeomorphic deformable registration method integrated with kernel regression in age. Deterministic tractography was performed to outline the forceps major, forceps minor, bilateral corticospinal tracts (CST), bilateral inferior fronto‐occipital fasciculus (IFOF), bilateral inferior longitudinal fasciculus (ILF), and bilateral uncinate fasciculus (UF). The mean fractional anisotropy (FA) and mean diffusivity (MD) was recorded for all tracts. For a subset of tracts (forceps major, CST, and IFOF) we manually divided the tractograms into anatomy conforming segments to evaluate within‐tract changes. We found tract‐specific, nonlinear, age related changes in FA and MD. Early in gestation, these trends appear to be dominated by cytoarchitectonic changes in the transient white matter fetal zones while later in gestation, trends conforming to the progression of myelination were observed. We also observed significant (local) heterogeneity in within‐tract developmental trajectories for the CST, IFOF, and forceps major. Diffusion‐atlas based tractography shows the white matter cytoarchitectonics drive diffusivity and anisotropy in the second and early third trimester and that myelination becomes a dominant factor in the mid to late third trimester. Further, these changes drive significant within‐tract heterogeneity.